Niedopasowanie do idei dobrego życia obszarem troski higieny - Marcinkowski, Jerzy Tadeusz (1948- ) - red.; Rosińska, Paulina - red.; Konopielko, Zofia - red.; Surendra, Sebastian; Klimberg, Aneta; Głowacki, Hieronim (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the monograph was to provide a comprehensive discussion of the perennial problem of stereotypes and violence against children and women, informed by the most current publications. Therefore, the monograph includes numerous chapters describing the history of treating children, including as sexual objects. Various types of violence, including domestic violence, affecting children and their consequences are discussed. It provides a historical outline of emerging children`s rights, with particular emphasis on Poland, current access to sex education (including in Germany), in the context of health, but also as a form of protection against teenage pregnancy.
Keywords: dzieci i młodzież; kobiety; historia; współczesność; stereotypy; przełamywanie; nauka; przemoc; prawo; altruizm; media; child; women; history; contemporary times; stereotypes; breaking; science; violence; rights; altruism